Reactivation of Hepatitis B Infection During the Cause of Non Hodgkin's Lymphoma Chemotherapy - Diana Jeni H; Syifa Mustika (The Indonesian Society for Digestive Endoscopy, 2014)
Hepatitis due to hepatitis B virus (HBV) reactivation after cytotoxic or immunosuppressive therapy is a serious cause of liver-related morbidity and mortality. Frequently used combination regimens in Non-Hodgkin’s lymphoma are cyclophosphamide, hydroxydaunomycin (adriamycin), vincristine (oncovin), and prednison (CHOP). The use of rituximab, a monoclonal antibody targeting CD20 antigen present in benign and malignant B-cells, in combination with systemic chemotherapy has resulted in an improved duration of remission and survival for this patients. Rituximab is a HBV reactivation risk factor even greater than corticosteroids in a series of patients with lymphoma treated with combined-modality treatment (CMT).A 43 years old female patient who already diagnosed with Non-Hodgkin’s lymphoma, came with chief complain nausea and vomiting for three weeks. The patient recently got hospitalized with icteric and known have positive HBsAg. She received chemotherapy rituximab CHOP (R-CHOP) for four times and got rituximab in the last chemotherapy. Previously she had icteric and increased liver function test. After exclude other possibility causes this symptom and sign, it was concluded this is HBV reactivation. The chemotherapy was postponed until this reactivation of hepatitis B resolved and start giving lamivudine two weeks before reintroduce chemotherapy.Keywords: antiviral treatment, chemotherapy, hepatitis B virus, reactivation